CHO’QMOR BILAN BAJARILADIGAN ULOQTIRISH VA ILIB OLISH MASHQLARINI O’RGATISH - Yusupova, M.A. (SCIENCE and SOCIETY, 2021)
The research hypothesis was confirmed during the study of the preparation of artistic gymnasts for throwing exercises performed with a club. Proposed by the developer, these techniques allow young athletes to identify and develop the ability to move in squats, which is typical for rhythmic gymnastics.
Keywords: physical training; special physical training; technical training; complex; exams